Psychiatry Trainees' Attitudes, Knowledge, and Training in Addiction Psychiatry—A European Survey - Orsolini, Laura; Rojnić Palavra, Irena; Papanti, Gabriele Duccio; Potočan, Matej; Quattrone, Diego; Martens, Matis; Sklenářová, Sandra; Levola, Jonna; Grichy, Leslie; Naughton, Sean; Grinevičiene, Indre Kotryna; Kuiters, Jelly Petra; et al. (Frontiers in Psychiatry, 2021)
Background. Although psychoactive substance use disorders are a domain of mental health, addiction psychiatry is only formally recognized as a subspecialty in few European countries, and there is no standardized training curriculum. Methods. A 76-item questionnaire was developed and disseminated through an online anonymous data-collecting system and hand-to-hand amongst psychiatric trainees in Europe from the 47 European countries of the Council of Europe plus Israel and Belarus. Results. 1,049/1,118 psychiatric trainees from 30 European countries completed the questionnaire. Fifty-nine-point nine percent of trainees stated to have training in addictions. Amongst the trainees who documented training in addictions, 43% documented a not well-structured training whilst 37% an unsatisfied training, mainly due to poor acquired knowledge. Overall, 97% of trainees stated that addiction represents a core curriculum for their training. Overall, general adult psychiatric trainees documented a better knowledge in addictions, compared to trainees in child and adolescent psychiatry. Conclusion. Despite a growing spread of psychoactive substance use disorders in European countries, addiction psychiatry is a relatively poorly trained field within psychiatry training program. Further research should investigate motivations of poor training and timings of educational activities to optimize experiential education training in addiction psychiatry.